2021
DOI: 10.12659/ajcr.930286
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Pembrolizumab-Induced Dermatomyositis in a Patient with Cancer of Unknown Primary Origin

Abstract: Patient: Female, 71-year-old Final Diagnosis: Dermatomyositis Symptoms: Fever • walking difficulties Medication: — Clinical Procedure: Corticosteroids Specialty: Immunology • Oncology • Rheumatology Objective: Rare disease Background: Pembrolizumab is a humanized monoclonal antibody against programmed cell death-1 protein. Pembrolizumab sometimes causes immune-related adverse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Interestingly, to the best of our knowledge, there is only a single published case of DM that resulted in disease resolution following treatment with immunotherapy [ 32 ]. The large majority of cases report DM as an adverse effect of ICI (pembrolizumab -carcinoma of unknown origin, squamous cell carcinoma of lung and lung adenocarcinoma; atezolizumab-in small cell lung cancer and non-small-cell lung cancer; nivolumab- lung adenocarcinoma and ipilimumab- small-cell lung cancer) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Bendewald et al have reported that the estimated incidence of DM is 9.63 cases per million people [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, to the best of our knowledge, there is only a single published case of DM that resulted in disease resolution following treatment with immunotherapy [ 32 ]. The large majority of cases report DM as an adverse effect of ICI (pembrolizumab -carcinoma of unknown origin, squamous cell carcinoma of lung and lung adenocarcinoma; atezolizumab-in small cell lung cancer and non-small-cell lung cancer; nivolumab- lung adenocarcinoma and ipilimumab- small-cell lung cancer) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Bendewald et al have reported that the estimated incidence of DM is 9.63 cases per million people [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…One has to be very careful by presenting the onset frequency of irAEs, as the numbers vary widely in the literature each based on different study models with their own limitations [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Managementmentioning
confidence: 99%
“…It shall be noted that by presenting the approximate onset frequency for irAEs in The same is going to be valid for the next two tables, in which I will present approximate timing of some selected irAEs and related CTCAE grading peak in monotherapy and combination therapy applications, and approximate onset frequency of irAEs with respect to organ/tissue systems in a CTLA-4/PD-1 combination therapy scenario, respectively. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In Table 3, again the weeks refer to weeks after the initial infusion and the damping time is as explained for Table 2 above.…”
Section: Provide In Tablementioning
confidence: 99%
“…Although several authors have reported dermatomyositis patients with cancer in whom the disease flares after the therapy with checkpoint inhibitor [ 43 46 ], this is not always the rule, and studies addressed to a better definition of those patients in whom immunotherapy will be suitable are being conducted. But this is only one side of the coin, the other side refers to those patients with cancer who develop an immune-mediated myopathy soon after the onset of immunotherapy.…”
Section: Treatmentmentioning
confidence: 99%